Selection and Validation of Reference Genes for RT-qPCR Analysis of the Ladybird Beetle Henosepilachna vigintioctomaculata - Lü, Jing; Chen, Shimin; Guo, Mujuan; Ye, Cuiyi; Qiu, Baoli; Wu, Jianhui; Yang, Chunxiao; Pan, Huipeng (Frontiers in Physiology, 2018)
Reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR) is a momentous technique for quantifying expression levels of the targeted genes across various biological processes. Selection and validation of appropriate reference genes for RT-qPCR analysis are a pivotal precondition for reliable expression measurement. Henosepilachna vigintioctopunctata is one of the most serious insect pests that attack Solanaceae plants in Asian countries. Recently, the transcriptomes of H. vigintioctopunctata were sequenced, promoting gene functional studies of this insect pest. Unfortunately, the reference genes for H. vigintioctopunctata have not been selected and validated. Here, a total of 7 commonly used reference genes, namely, Actin, GAPDH, RPL13, RPL6, RPL32, RPS18, and ATPB, were selected and assessed for suitability under four experimental conditions, namely, developmental stage, tissue, temperature, and host plant, using RefFinder, which integrates four different analytical tools (Normfinder, geNorm, the ΔCt method, and BestKeeper). The results displayed that RPL13 and RPS18 were the best suitable reference genes for each experimental condition. The relative transcript levels of 2 target genes, lov and TBX1, varied greatly according to normalization with the two most- and least-suited reference genes. Our results will be helpful for improving the accuracy of the RT-qPCR analysis for future functional investigations of target gene expression in H. vigintioctopunctata.